Fostering culinary diversification, food hygiene, and sanitation: A community outreach initiative for MSMEs - Yoanita Alexandra; Ringkar Situmorang; Dinar Ajeng Kristiyanti (University of Merdeka Malang, 2023)
This paper highlights a community outreach program aimed at promoting culinary diversification, enhancing food hygiene, and fostering sanitation practices among Culinary Micro, Small, and Medium Enterprises (MSMEs) in Serdang Wetan Village under BUMDES (Village-owned enterprise) Serdang Tirta Kencana, Tangerang, Indonesia. The primary objective of the outreach activities was to empower MSMEs with knowledge and skills to diversify their culinary offerings while ensuring compliance with essential food safety standards and sanitation guidelines. Through a cooking workshop and interactive demonstrations, participating MSMEs were introduced to new recipes, cooking techniques, and ingredient combinations that would enhance their menu options. The program also strongly emphasized food hygiene and sanitation practices to minimize the risk of foodborne illnesses and uphold public health standards. Participants received comprehensive training on proper food handling, storage, and preparation techniques, emphasizing maintaining a clean and hygienic environment within their establishments. Overall, this program underscores the significance of community-driven initiatives in bolstering culinary diversification, food hygiene, and sanitation for MSMEs. By fostering a culture of continuous learning and collaboration, this outreach program holds the potential to promote sustainable development and elevate the food industry in Serdang Wetan Village while ensuring the health and well-being of its residents and visitors alike.